Specifics of forming linguistic sociocultural competence among foreign students in the pre-university period - Yurova, Yuliya (2021)
The article considers communicative competence as a sum of several competences such as linguistic, paralinguistic, linguistic-sociocultural, substantial competences, etc. Linguistic sociocultural competence is specifically featured. The article describes linguistic cultural, psychosocial and cultural expertise and skills. The criteria of learning material selection for the formation of linguistic sociocultural competence.